4x-1/3+(2x-1/2)(-3x-7/5)=6

Simple and best practice solution for 4x-1/3+(2x-1/2)(-3x-7/5)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-1/3+(2x-1/2)(-3x-7/5)=6 equation:



4x-1/3+(2x-1/2)(-3x-7/5)=6
We move all terms to the left:
4x-1/3+(2x-1/2)(-3x-7/5)-(6)=0
We can not solve this equation

You can always share this solution

See similar equations:

| -15x-12+12x+6=-21 | | b2-6b-16=0 | | -4x-6-14x+15=-225 | | 47=1.42x+12.6747=1.42x47+12.67 | | 3/2x=-13/4+4 | | 2d+4d=30 | | 9k2+7k+16=0 | | x^2=4-6x | | x2=4-6x | | 5x-1/3=3x-1 | | x-3^2=4096 | | 3(5x+1)=2(2x-6) | | 3a+2=11a-6 | | 625^x-2=(5)^2x-10 | | 4x*2+8x-9=0 | | 11x=3x^2-9 | | 2^2s=50 | | 3x(1-2x)=16 | | 11x=3x2-9 | | 11x=3x-9 | | X+2x+9x=156 | | r^-100=0 | | X=2/7(180-x) | | a=-4a+10 | | x^2+3x-0.64=0 | | 8^(x-2)×(1/2)^(4-3x)=(0.0625)^x | | 3(x-1)-2(3-x)=1 | | x2+0x-0.25=0 | | 5x+3=427 | | 4k^2+16k=-7 | | 7t-3÷4t=18 | | (5x+3)(x-1)=5x^2 |

Equations solver categories